PELEPASAN KURKUMIN DARI NANOPARTIKEL KITOSAN-KARBOKSIMETIL SELULOSA-GLUTARALDEHIDA - , PRAPTANTI SINUNG A.N; , Dr. Dwi Siswanta, M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The releasing kinetic of curcumin in chitosan-carboxymethyl cellulose nanoparticles crosslinked with glutaraldehyde has been studied. Identification of functional groups was determined by Fourier Transform Infrared (FTIR) spectrophotometry method. The crystallinity characteristic was tested by X-Ray Diffraction (XRD). Particle size determination was performed using Transmission Electron Microscopy (TEM), whereas the morphological characterization was tested by Scanning Electron Microscopy (SEM). Studyof curcumin release was determined by UV-Vis spectrophotometer. In this research, the effects of chitosan, KMS, and glutaraldehyde (GA) concentration were studied. Kinetics model of zero order, first order, Higuchi, and Korsmeyer-Peppas were used to test the kinetics of curcumin release. The results showed that the electrostatic interaction between the amine group with a carboxyl group can cause a shift in the uptake of chitosan-KMS-GA nanoparticles at wave number 1589 cm -1 . Nanoparticles have a size of Â±70 nm. The composition of chitosan-KMS-GA nanoparticles concentration obtained at the optimum ratio 3:1:0.8. Model equation of curcumin release followed Korsmeyer-Peppas kinetics with the Fickian diffusion mechanism. Curcumin release of 53.82% as much happened for 5 hours.